Modeling of meltwater runoff on the example of the Nura river section from Samarkand to Intumak reservoirs (Journal of Geography and Environmental Management, 2021)
The Nura River basin is characterized by an uneven intra-annual distribution of runoff, 90 % of the river runoff falls on the spring flood, while it should be noted that a distinctive characteristic feature of the Nura River basin is that the flood runoff is formed due to snow melt runoff. Information about meltwater runoff is necessary when predicting a flood situation for a short and long-term period in industrial production, since this is a very urgent problem for the territory of Kazakhstan. Thawed runoff is one of the main factors in the formation of river flow, with heavy snowmelt-it is one of the main reasons for the formation of flooding, flooding and flooding. In this regard, the modeling of melt runoff is an urgent and significant task. Snow cover plays an important role in the interaction of climatic, hydrological and glaciological processes. Snow is a powerful climate-forming factor that has a significant impact on the formation of weather conditions. One of the most important characteristics of the snow cover is the water supply, or water equivalent, also called melt runoff. Therefore, the subject of the study was the modeling of melt runoff. The purpose of the article is forecasting and modeling of melt runoff on the example of the Nura River section from the Samarkand to Intumak reservoirs with the study of data for the period from 01.11.2013 to 01.04.2014 and the forecast of modeling from 1.04.2014 to 06.04.2014. The study period was not chosen by chance. Since during the analysis of data and characteristics for this site, it was the period of 2014 that was one of the most high-water years. In this connection, the above-mentioned study period was chosen. The research was carried out on the basis of the data of the RSE "KazHydromet" on hydrological and meteorological indicators and a digital relief model.